Making Use of YouTube for English Speaking Skill Enhancement: Pre-Service Librarians’ Practices and Perceptions - Dalilan, Dalilan; Mulyadi, Mulyadi; Nuraini, Nuraini (Perkumpulan Dosen dan Pengajar Bahasa Inggris Se-Indonesia (ELITE Association Indonesia), 2024)
YouTube is nowadays well known as a social media platform in the Internet. This advanced technology-based application is freely used by all people, including by both school students and university students. The objective of this study was to investigate pre-service librarians’ practices and perceptions on using YouTube to encourage their skills in English speaking practices. This study was designed as a qualitative descriptive study using a question survey with two options (Setuju and Tidak Setuju) to collect data. The data were collected from 66 students of Library Science Study Program at Faculty of Humanities, UIN Raden Fatah Palembang. These students are at second semester participating in the course of English for librarian in the ongoing semester. Data from the survey were analyzed by using thematic analysis. The result of the study indicated that all research participants preferred to speaking lesson more than other lessons such as reading, listening, and writing. In addition, they were considerably encouraged to post their speaking recorded videos in YouTube platform as their English self-assets in the online environment. They have made use of such recorded videos of English speaking practices the learning media to improve their English speaking skills. In conclusion, speaking practices using English recorded and uploaded to YouTube were perceived as the path for the students to be fond of English communication and benefit them to enhance their English speaking skill for future career as a librarian.